Estudo morfológico de duas populações de Hoplias grupo malabaricus (Characiformes: Erytrinidae) procedentes da Bacia do Rio Grande, Estado de São Paulo - Pacheco, Mariana Rodrigues (Universidade Federal de São Carlos, 2004)
In the present research, 116 specimens of Hoplias sp. (Erythrinidae: Characiformes) from Grande river basin, São Paulo state (Alto-Paraná basin) were morphologically analyzed. They are all representants of malabaricus group , which can be distinguished of lacerdae group mainly by the shape of dentary region, and the number of pores in each dentary. From each fish analyzed, it was obtained 24 meristic and 33 morphometric data. The osteological analysis was realized in four exemplars of Pardo river basin. In the studied sample, it was found two different species, and they are sympatric in the majority of localities. These results corroborate with cytogenetic studies, which demonstrated two different citotypes in Grande river basin. This way, a description was realized for the species, that in this work are named Hoplias sp. A and Hoplias sp. B. They can be distinguished one from another by a combination of characteristics, mainly the shape and the number of teeth in the accessory ectopterigoid and the proportions and distribution of infraorbitals. Morphological differentiation among them was analyzed by the principal component analysis, and the results indicate differences in body form.
Keywords: Ictiologia; Erytrinidae; Taxonomia; Bacia do Rio Grande; CIENCIAS BIOLOGICAS::ECOLOGIA